The Multifaceted Roles of Autophagy in Infectious, Obstructive, and Malignant Airway Diseases - Marianna Carinci; Laura Palumbo; Giulia Pellielo; Esther Densu Agyapong; Giampaolo Morciano; Simone Patergnani; Carlotta Giorgi; Paolo Pinton; Alessandro Rimessi (Biomedicines, 2022)
Autophagy is a highly conserved dynamic process by which cells deliver their contents to lysosomes for degradation, thus ensuring cell homeostasis. In response to environmental stress, the induction of autophagy is crucial for cell survival. The dysregulation of this degradative process has been implicated in a wide range of pathologies, including lung diseases, representing a relevant potential target with significant clinical outcomes. During lung disease progression and infections, autophagy may exert both protective and harmful effects on cells. In this review, we will explore the implications of autophagy and its selective forms in several lung infections, such as SARS-CoV-2, Respiratory Syncytial Virus (RSV) and Mycobacterium tuberculosis (Mtb) infections, and different lung diseases such as Cystic Fibrosis (CF), Chronic Obstructive Pulmonary Disease (COPD), and Malignant Mesothelioma (MM).